Associations between home death and GP involvement in palliative cancer care - Neergaard, Mette A (Royal College of General Practitioners, 2009)
BACKGROUND: Most cancer patients die at institutions despite their wish for home death. GP-related factors may be crucial in attaining home death. AIM: To describe cancer patients in palliative care at home and examine associations between home death and GP involvement in the palliative pathway. DESIGN OF STUDY: Population-based, combined register and questionnaire study. SETTING: Aarhus County, Denmark. METHOD: Patient-specific questionnaires were sent to GPs of 599 cancer patients who died during a 9-month period in 2006. The 333 cases that were included comprised information on sociodemography and GP-related issues; for example knowledge of the patient, unplanned home visits, GPs providing their private phone number, and contact with relatives. Register data were collected on patients' age, sex, cancer diagnosis, place of death, and number of GP home visits. Associations with home death were analysed in a multivariable regression model with prevalence ratios (PR) as a measure of association. RESULTS: There was a strong association between facilitating home death and GPs making home visits (PR = 4.3, 95% confidence interval [CI] = 1.2 to 14.9) and involvement of community nurses (PR = 1.4, 95% CI = 1.0 to 1.9). No other GP-related variables were statistically significantly associated with home death. CONCLUSION: Active involvement of GPs providing home visits and the use of home nurses were independently associated with a higher likelihood of facilitating home death for cancer patients. The primary care team may facilitate home death, accommodating patients' wishes. Future research should examine the precise mechanisms of their involvement.